2018
DOI: 10.1093/ptep/pty006
|View full text |Cite
|
Sign up to set email alerts
|

Spherical D-brane by tachyon condensation

Abstract: We find a novel tachyon condensation which provides a D-brane system with spherical worldvolume in the flat spacetime. The tachyon profile is a deformation of a known D0-brane solution on non-BPS D3-branes in type IIA superstring theory, which realizes a bound state of a spherical D2-brane and a D0-brane. The D0-brane is resolved into the sphere as a U (1) monopole flux of the unit magnetic charge. We show that the system has the correct tension and the RRcoupling. Although the low energy effective action of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Recently, in Refs. [22,23], the authors showed that the magnetic flux may come from the tachyon condensations induced from the dynamics of D-branes and non-BPS D-branes. We expect that our results can be described by the full dynamics of the IKKT model.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recently, in Refs. [22,23], the authors showed that the magnetic flux may come from the tachyon condensations induced from the dynamics of D-branes and non-BPS D-branes. We expect that our results can be described by the full dynamics of the IKKT model.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the case that the tachyon potential has the form (2.8), this gauge field is also confined to the region M ⊂ R 3 because of the delta-function distribution. In this case, (2.12) has components only along M (for the proof, see [22]). If U(x) is not globally defined and there are two different diagonalizations {U I (x)} at a point, then two gauge potentials of the form (2.12) are related by U(1) transition function.…”
Section: )mentioning
confidence: 98%
“…The resulting defect should be the deformation of the point-like defect by matrices Φ. Indeed, as shown in [22], a deformation of the single D0-brane (k = 1) profile drastically changes the condensation defect to a spherical D2-brane 1 . Our claim in this paper is that the position or the shape of D-branes is determined by diagonalizing the tachyon field T , not the scalar fields Φ themselves.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations